On the Sacrament of the Eucharist in the Collection of Sermons Punkty kazań by Konstantinas Sirvydas in Comparison to Piotr Skarga’s Sermons - Paluszak - Bronka, Anna (Slavistica Vilnensis, 2018)
[full article, abstract in Polish; abstract in Lithuanian and English]The current paper describes Eucharist terminology used in Punkty Kazań by Konstantinas Syrvidas in comparison to nomenclature used by a Polish Jesuit, Piotr Skarga. The author demonstrates how both preachers, writing about the same sacrament, never created proper nouns; they used terminology from the Old and the New Testament, as well as from the scholarly books of the Church, accepted by the Vatican Councils. Notwithstanding the foregoing, Syrvidas nomenclature is poor and homogenous in comparison to Skarga’s one. The author thinks that there are several reasons justifying that problem: Syrvidas wrote Points [Punkty] without any elaboration where he referred to the text of the Holy Bible and the teachings of the Church Fathers; in his turn Skarga addressed his teachings not only to educated people who were to carry God’s word to others, but to the common people, among whom many pagans still remained; Syrvidas’ Points meant to enlighten, whereas Skarga’s goal was to argue. It was probably due to the fact that in the 17th century, religious disputes were less ardent than before; it is also possible that this sermon has been written by someone else and was added to the 2nd volume of the Points.
Keywords: sermon, Eucharist, Jesuit teachings, Piotr Skarga, Konstantinas Syrvidas